2020
DOI: 10.1002/bit.27346
|View full text |Cite
|
Sign up to set email alerts
|

Molecular binding scaffolds increase local substrate concentration enhancing the enzymatic hydrolysis of VX nerve agent

Abstract: Kinetic enhancement of organophosphate hydrolysis is a long‐standing challenge in catalysis. For prophylactic treatment against organophosphate exposure, enzymatic hydrolysis needs to occur at high rates in the presence of low substrate concentrations and enzymatic activity should persist over days and weeks. Here, the conjugation of small DNA scaffolds was used to introduce substrate binding sites with micromolar affinity to VX, paraoxon, and methyl‐parathion in close proximity to the enzyme phosphotriesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In order to explain the enhancement of the catalytic kinetics of a single enzyme, the pH profile near the DNA surface was modeled, and it was concluded that the pH might have a critical effect on enzymatic activity . Moreover, research also showed that HRP and phosphotriesterase’s , activities can be improved by increasing the affinity of substrates on negatively charged DNA motifs, implying that the polyanionic DNA material could promote enzymatic activity through altering local chemical and physical microenvironments.…”
mentioning
confidence: 99%
“…In order to explain the enhancement of the catalytic kinetics of a single enzyme, the pH profile near the DNA surface was modeled, and it was concluded that the pH might have a critical effect on enzymatic activity . Moreover, research also showed that HRP and phosphotriesterase’s , activities can be improved by increasing the affinity of substrates on negatively charged DNA motifs, implying that the polyanionic DNA material could promote enzymatic activity through altering local chemical and physical microenvironments.…”
mentioning
confidence: 99%
“…[47][48][49][50] However, here the underlying contributing factors are more complex and appear to be associated with the influence of DNA's strongly charged environment leading to localized sequestration of substrate or intermediaries along with perhaps making the reaction environment more favorable in certain cases. [51,52] There has been, and still continues to be, considerable scientific debate around the origins and complexity surrounding such phenomena. [53,54] Previous studies of enzymatic enhancement on NP scaffolds in the context of a coupled enzymatic system revealed that enzyme stabilization could also contribute to the observed catalytic increases.…”
Section: Enzymatic Enhancement On Nanoscaffolds and Channelingmentioning
confidence: 99%
“…with N-acyl homoserine lactones [108,109]. Thus, they can be rationally combined to obtain universal enzyme preparations [110] or even hybrid molecules with other enzymes [111] or with 'guide' DNA [112]. This opens up new promising perspectives for their practical application.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%